Real‐time electromagnetic navigation for breast‐conserving surgery using NaviKnife technology: A matched case‐control study. Issue 3 (17th September 2019) - Gauvin, Gabrielle; Yeo, Caitlin T.; Ungi, Tamas; Merchant, Shaila; Lasso, Andras; Jabs, Doris; Vaughan, Thomas; Rudan, John F.; Walker, Ross; Fichtinger, Gabor; Engel, Cecil Jay
Abstract: Breast‐conserving surgery (BCS) is a mainstay in breast cancer treatment. For nonpalpable breast cancers, current strategies have limited accuracy, contributing to high positive margin rates. We developed NaviKnife, a surgical navigation system based on real‐time electromagnetic (EM) tracking. The goal of this study was to confirm the feasibility of intraoperative EM navigation in patients with nonpalpable breast cancer and to assess the potential value of surgical navigation. We recruited 40 patients with ultrasound visible, single, nonpalpable lesions, undergoing BCS. Feasibility was assessed by equipment functionality and sterility, acceptable duration of the operation, and surgeon feedback. Secondary outcomes included specimen volume, positive margin rate, and reoperation outcomes. Study patients were compared to a control group by a matched case‐control analysis. There was no equipment failure or breach of sterility. The median operative time was 66 (44‐119) minutes with NaviKnife vs 65 (34‐158) minutes for the control ( P  = .64). NaviKnife contouring time was 3.2 (1.6‐9) minutes. Surgeons rated navigation as easy to setup, easy to use, and useful in guiding nonpalpable tumor excision. The mean specimen volume was 95.4 ± 73.5 cm 3 with NaviKnife and 140.7 ± 100.3 cm 3 for the control ( P  = .01). The positive margin rate was 22.5% with NaviKnife and 28.7% for the control ( P  = .52). The re‐excision specimen contained residual disease in 14.3% for NaviKnife and 50% for the control ( P  = .28). Our results demonstrate that real‐time EM navigation is feasible in the operating room for BCS. Excisions performed with navigation result in the removal of less breast tissue without compromising postive margin rates.